Exploring Gender Identity and Discrimination in Digital Age (International Journal of Scientific Research in Science and Technology, 2024)
Digital age has an enormous landscape of thoughts and studies, and its boundaries are expanded to explore more unvoiced topics too. Accordingly gender studies have taken a major form in this enduring digital age. Digital media and other digital platforms have shaken hands for both amplified opportunities as well as deterioration of traditional gender norms of the society. This paper directly expresses the deed of digital technologies shaping the gender identities; voice the voiceless, gender equality of women and visibility of newbie communities like LGBTQ. And also it particularly addresses the challenges of generational understanding of sexuality and gender. Focus is not only lighted up in these aspects but it also focuses on the theories like queer theory, feminist theory and many other theories that stand as a dominant theme of gender studies. Gender studies also has its own dark side such as digital harassment, gendered digital divides, digital violence and threatening, sometimes freedom of speech can also extend to a shoddier reputation. Even though opportunities are created to express gender, to create connection and also activism of both the gender, it has also created many new-fangled forms of discrimination that gambol the eyes of a common living-being. Women, transgender and marginalised communities are the most common groups that witness discrimination in digital age. To address and resolve these problems we need a combination of change in people’s thinking as well as policies of the tech creators.